Organic food and gastronomy (Journal of Namibian Studies : History Politics Culture, 2023)
Currently, the gastronomic and service sector has increased the offer of dishes that include organic products in the menus of its restaurants. The growing variation of different types of diets such as vegan, gluten-free, paleo, or even those who opt for a diet with 0 km and seasonal products has been reason enough for the creation of ecogastronomy. Ecogastronomy refers to the application of ecological principles when selecting the ingredients used to prepare different dishes, both in domestic preparations and in collective catering, as well as in haute cuisine. Thus, one of the bases of organic gastronomy is the choice of organic products for cooking, betting on a lifestyle that promotes sustainable development, preferring foods grown in proximity. One of the greatest contributions of ecogastronomy and 'ecochefs' is in preserving biodiversity, expanding the range of food produced and consumed, creating trends in eating habits and reintroducing species and varieties in consumption. Species and varieties adapted to organic production have a higher nutritional content.